Case Report: Kasai Operation in Biliary Atresia After Extensive Bowel Resection - Chen, Szu-Han; Chang, Kai-Chi; Wu, Jia-Feng; Chen, Huey-Ling; Lin, Wen-Hsi (Frontiers in Surgery, 2022)
Biliary atresia is a major and devastating cholestatic liver disease in infancy. The Kasai procedure is an operation to re-establish bile flow from the liver into the intestine that can prevent the young infant from progressing rapidly to cirrhosis. The standard Kasai procedure include removal of extrahepatic bile duct remnants and reconstruction. We report a case of biliary atresia with short bowel due to previous small intestinal volvulus. This full-term female infant received extensive small bowel resection after birth due to intestinal volvulus. The length of the residual small bowel was 55 cm with intact ileocecal valve. Because of progressive cholestasis and clay stool, another laparotomy was performed under the diagnosis of biliary atresia on the 52 days old. After dissection of the hepatic portal area, a segment of colon instead of intestine was used as biliary conduit to avoid further shortening her small bowel. The patient recovered from the procedure uneventfully and the parenteral nutrition was discontinued 2 weeks later. Two episodes of cholangitis happened after discharge. She gradually resumed body weight gain and the bilirubin level returned to normal range 6 months after the operation. This unique case demonstrated a successful use of this specific procedure in the patient with BA and short bowel that have never been reported in the literature.